2019
DOI: 10.1097/md.0000000000016105
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repetitive transcranial magnetic stimulation on the whole-brain functional network of postherpetic neuralgia patients

Abstract: The effects of repetitive transcranial magnetic stimulation (rTMS), the clinical treatment for postherpetic neuralgia (PHN), on whole-brain functional network of PHN patients is not fully understood. To explore the effects of rTMS on the whole-brain functional network of PHN patients. 10 PHN patients (male/female: 5/5 Age: 63–79 years old) who received rTMS treatment were recruited in this study. High-resolution T1-weighted and functional Magnetic Resonance Imaging (fMRI) were acquired be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The motor cortex is one of the most frequently reported stimulation targets for rTMS modulation in both healthy populations (Hartwigsen and Siebner, 2015;Cona et al, 2017) and those with brain disorders including movement disorders (Wagle Shukla et al, 2016;Brabenec et al, 2019), stroke rehabilitation (Ludemann-Podubecka et al, 2016;Lee et al, 2019), and other disorders (Siebner et al, 2003;Odorfer et al, 2019;Pei et al, 2019;Zhang et al, 2019). Some of these studies performed RS-fMRI before and after modulation and analyzed the network changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor cortex is one of the most frequently reported stimulation targets for rTMS modulation in both healthy populations (Hartwigsen and Siebner, 2015;Cona et al, 2017) and those with brain disorders including movement disorders (Wagle Shukla et al, 2016;Brabenec et al, 2019), stroke rehabilitation (Ludemann-Podubecka et al, 2016;Lee et al, 2019), and other disorders (Siebner et al, 2003;Odorfer et al, 2019;Pei et al, 2019;Zhang et al, 2019). Some of these studies performed RS-fMRI before and after modulation and analyzed the network changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is large variation in the analytical methods applied from study to study. These included voxel-to-voxel based dynamic FC , graph theory using 24 ROIs (Lee et al, 2019), whole-brain graph theory (Pei et al, 2019), and seed-based FC (Brabenec et al, 2019). While it could be concluded that rTMS of the motor cortex modulates the motor network, such a conclusion appears too general since it is difficult to identify which specific brain areas are modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, it is ambiguous that how rTMS with different intensities, at different frequencies, can modulate the neural circuit activities, such as the neural plasticity which is one of the most important characters of the neural function, because of the limitation of animal models. Cultured neurons [10,11] and hippocampal slices [12] from rats and even humans [13,14] have been utilized to study the role of rTMS. However, these models are difficult to present a complete loop neural circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The thalamus is the information integration center in the brain and is in the cortical-striatum-thalamus pathway ( 48 ). Therefore, impaired nodal metrics of basal ganglia and thalamus might be indirectly modulated by the stimulation of the cortical areas ( 49 ). The treatment of rTMS could modulate brain structural networks in children with BSCP and the modulated brain regions were associated with the improved motor and cognitive symptoms.…”
Section: Discussionmentioning
confidence: 99%